Geographical distribution of authorship for leading cardiothoracic surgery journals. Issue 12 (13th October 2022) - Gupta, Aashray K.; Ovenden, Christopher D.; Nathin, Kayla; Aujayeb, Nidhi; Hewitt, Joseph N.; Kovoor, Joshua G.; Chan, Justin C. Y.; Wells, Adam
Abstract: Background: Evolution of surgical practice is influenced by publications in the leading journals of that field. If the authorship of a publication lacks geographical diversity, this could create bias and limit generalizability of the evidence. Accordingly, we conducted a geographical analysis of the leading Cardiothoracic Surgery journals worldwide. Methods: Using 2020 Impact Factor, we searched the leading Cardiothoracic Surgery journals over the past decade. Only original articles were included. Data regarding first, second and last authors were extracted from every article. From this, we analysed country of affiliation, highest academic degree obtained and author location by metropolitan or rural setting. Results: A total of 12, 706 original articles were published in the top 5 ranked Cardiothoracic journals between 2011 and 2020. Authors originated from 69 countries, with the majority being from North America and Western Europe. The United States was the most common country of affiliation (42.8%) in all five journals, with New York City the most prominent city. A total of 63.7% of the authorship originated from large metropolitan areas (estimated as population greater than 500, 000 residents), and the most common degrees obtained by authors were MD and PhD. Conclusion: The prominent Cardiothoracic authorship is predominantly located in Western countries, most commonly large metropolitan centers in the United States. This raises questions as to whether the literature adequately reflects populations in other geographical areas such as the continents of South America and Africa and rural settings. Leading journals should consider policies which encourage publication by authors from geographical locations that are underrepresented globally.